Teaching Local Wisdom through Oral Literature: Insights from Teachers’ Beliefs and Practices on Minangkabau Petatah-Petitih - Pratama, Rizki Haryadi; Yandra, Afikah (Jurnal Tahuri, 2025)
This study investigates the teaching of local wisdom through oral literature by examining Minangkabau petatah-petitih (traditional proverbs) in relation to teachers’ beliefs and classroom practices. Indonesian literary education often prioritizes national and canonical texts while giving limited attention to local oral traditions that embody moral, cultural, and philosophical values. Using a qualitative case study approach at MAN 3 Batusangkar, West Sumatra, the research involved Indonesian language teachers and Grade XI students. Data were gathered through in-depth interviews, classroom observations, and analysis of instructional documents, and were analyzed thematically to identify patterns of belief, practice, and tension. Findings show that teachers value petatah-petitih as a pedagogical resource for fostering character education and cultural awareness, but face structural constraints from a nationally oriented curriculum that provides little space for local oral traditions. While some teachers integrate petatah-petitih into classroom activities, discrepancies often arise between their beliefs and instructional realities. The novelty of this study lies in shifting the discourse on petatah-petitih from cultural and textual analysis toward its application as a living educational resource. The research highlights the potential of oral traditions as tools for critical literacy, cultural identity reinforcement, and pedagogical innovation, underscoring the need for culturally responsive curricula and teacher training.